2002
DOI: 10.1038/sj.bmt.1703680
|View full text |Cite
|
Sign up to set email alerts
|

Immune reconstitution after haematopoietic transplantation with two different doses of pre-graft antithymocyte globulin

Abstract: Summary:Antithymocyte globulin is widely used before haematopoietic transplantation with HLA-matched unrelated donors or mismatched relatives to prevent rejection and graft-versus-host disease (GVHD). However, optimal dosage is still under debate. Thirty-one consecutive children, mainly with haematological malignancies, were transplanted in a single institution with such donors, selected by HLA-A -B compatibility by serology and DRB1* by DNA typing. Antithymocyte globulin (Thymoglobuline; Sangstat) was infused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 18 publications
3
24
0
Order By: Relevance
“…2,14 The propensity of patients receiving 10 mg/kg ATG to contract severe virus-related infections is associated with significantly lower lymphocyte counts on day 30. Duval et al 22 reported similar results. Although it was not prospectively subject to any hypothesis, the clinical significance of this result deserves further prospective investigation.…”
Section: Discussionsupporting
confidence: 77%
“…2,14 The propensity of patients receiving 10 mg/kg ATG to contract severe virus-related infections is associated with significantly lower lymphocyte counts on day 30. Duval et al 22 reported similar results. Although it was not prospectively subject to any hypothesis, the clinical significance of this result deserves further prospective investigation.…”
Section: Discussionsupporting
confidence: 77%
“…The median time to CD3 þ count of 41000/ml was 7 months in patients who received 7.5 mg/ kg of rATG in Duval's study, 25 compared to 5.3 months in our study. Duval indicated that the time to recovery of T cell immunity was related to the rATG dose.…”
Section: Discussionmentioning
confidence: 75%
“…Immune reconstitution in children undergoing unmanipulated unrelated and mismatched related donor transplants receiving different doses of rATG was studied by Duval et al 25 In their study, a higher dose of rATG (median 15.5 mg/kg) was related to significant delay in immune reconstitution. The median time to CD3 þ count of 41000/ml was 7 months in patients who received 7.5 mg/ kg of rATG in Duval's study, 25 compared to 5.3 months in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many protocols have been used, and some comparisons made in non-randomized studies. [24][25][26][27][28] However, the impact of different protocols on lymphoid depletion and recovery has not been properly evaluated, 29 although some differences in lymphocyte recovery have been noted. 25,26 We prospectively evaluated three different serotherapy schedules with a single prospective protocol on adjusted conditioning of 69 patients with a median age of 54 years, and mainly with high-risk hematological malignancies, in a single institution.…”
Section: Discussionmentioning
confidence: 99%